Adherence to follow‐up recommendations for dogs with apocrine gland anal sac adenocarcinoma: A multicentre retrospective study. (3rd May 2020) - Chambers, Aidan R.; Skinner, Owen T.; Mickelson, Megan A.; Schlag, Ariel N.; Butler, James Ryan; Wallace, Mandy L.; Moyer, Ashley L.; Vinayak, Arathi; Samuel, Nina; Kennedy, Katie C.; Oakes, Katherine E.; Scharf, Valery F.; et al.
Abstract: Progressive disease is common following anal sacculectomy for apocrine gland anal sac adenocarcinoma (AGASACA); additional therapy may prolong survival. Adherence to medical recommendations influences therapeutic success in humans. The purpose of this study was to assess the adherence to follow‐up recommendations in dogs with AGASACA. Medical records of patients that underwent anal sacculectomy for AGASACA, with or without iliosacral lymphadenectomy, between July 2015 and July 2018, were reviewed at eight referral institutions to assess post‐operative recommendations and owner adherence to recommendations. One hundred and seventy‐four dogs were included, of which 162 underwent unilateral anal sacculectomy, 12 underwent bilateral anal sacculectomy and 39 underwent concurrent iliosacral lymphadenectomy. Seventy‐six owners (44%) received recommendations for staging at the time of discharge, histopathology results or at the first follow‐up visit. One hundred and forty owners (80%) received recommendations for treatment following the initial surgery. Fifty of seventy‐six (66%) owners pursued at least one staging recommendation and 69 of 140 (49%) owners pursued some kind of adjuvant treatment recommendation. Overall, 16 of 76 (21%) were adherent to staging recommendations with 20 adherent for the first year following surgery (26%). Forty‐seven of 140 (34%) were adherent to treatment recommendations with 54 (39%) adherent for the first year. Owners that were adherent to restaging recommendations at 1 year following surgery were significantly more likely to pursue treatment for progressive disease ( P = .014). Further work is required to assess owner motivation and evaluate strategies to improve adherence, given the potential impact on patient treatment.